The Heat Source Origin of Geothermal Resources in Xiong’an New Area, North China, in View of the Influence of Igneous Rocks - Cui, Yue; Zhu, Chuanqing; Qiu, Nansheng; Tang, Boning; Guo, Sasa; Lu, Zhiwei (Frontiers in Earth Science, 2022)
Xiong’an new area has abundant geothermal resources, and heat source research plays an important role in the geothermal system. Using the logging curve, we calculated the radioactive heat production of sedimentary layers and igneous rocks in non-sample wells, analyzed the influence of igneous rock distribution, residual heat, and its thermal increment on crust, and clarified the heat source origin of hydrothermal geothermal resources in Xiong'an new area. Sedimentary layers data (5504) of 20 wells were converted to determine the applicable GR-A empirical relationship and the radioactive heat production of igneous rocks with different lithologies was estimated. Finite element simulations show that igneous rock intrusions in the study area reach thermal equilibrium with the surrounding rock after 0.5Ma at most. Upon cooling, the difference in thermal physical properties to the surrounding rock only leads to a higher heat flow of about 3.55mW/m2 in the partial of the Niutuozhen salient. It is known that the development of igneous facies impacts the heat source. Under the geothermal background of "cold crust-hot mantle", the mantel heat was the primary source, which the Yanshanian intrusions injected into the central salient, increasing the crustal heat by about 12%, and the heat source by about 6%. The measured heat flow becomes higher in the salient (raised about 12.04mW/m2-29.25mW/m2) where the deep faults developed due to the groundwater convection. Heat conduction from crust-mantle heat flow and heat convection caused by deep faults are responsible for the current geothermal state in Xiong'an new area.